Evaluation of global remotely sensed evapotranspiration products in arid irrigated agricultural environments using ground measurements - Phathutshedzo Eugene Ratshiedana; Mohamed A. M. Abd Elbasit; Elhadi Adam; Johannes George Chirima (Geocarto International)
Accurate quantification of crop water requirement is essential for efficient irrigation practices. However, direct measurement of crop water use is localised and impractical over large areas. Remotely sensed evapotranspiration (ET) provides a solution by estimating spatial explicit ET. Nevertheless, the accuracy of ET products in South African irrigated agriculture remains uncertain. This study evaluated the accuracy of MODerate Resolution Imaging Spectroradiometer (MOD16), Noah Land Surface Model Evapotranspiration Product (NOAH) and Water Productivity Open-access Portal (WaPOR) products retrieved using Google Earth Engine (GEE). A stepwise validation approach was applied integrating lysimeter-derived actual evapotranspiration (ETa) with reference evapotranspiration (ETo) to extrapolate ETa across the Vaalharts irrigation scheme. Results demonstrated WaPOR as a promising product with correlations of 0.69 to 0.88, and lower errors with RMSE from 0.87 to 3.22 mm d−1, while MOD16 and NOAH estimates are poor. These findings demonstrate WaPOR as a potential tool for improving irrigation water management.